Analysis of Behavioral Finance, Financial Literacy and Their Impact on Financial Distress - Mahmud Yusuf Afif; Muhammad Sulhan (Universitas Islam Kadiri, 2022)
This study aims to determine the effect of financial literacy and financial behavior on financial distress students of the Faculty of Economics, State Islamic University of Malang. The type of research used is quantitative research. The research location appointed by the researcher is at the State Islamic University (UIN) Maulana Malik Ibrahim Malang. The number of samples in this study were 130 respondents. The sample in this study was Generation Z who were born in 1996 – 2004 or who are 18-26 years old and actively hold the status of students of the Faculty of Economics, State Islamic University (UIN) Maulana Malik Ibrahim Malang. The variables used in this study consisted of independent variables and dependent variables. The dependent variable is financial distress, while the independent variables are financial literacy and financial behavior. The data that has been obtained were analyzed using SPSS ver. 20.0. Based on the results of the research that has been obtained, it can be concluded that tax knowledge, fiscal services, and administrative sanctions have a positive and significant effect (1) financial literacy has a negative and significant effect on financial distress, (2) financial behavior has a negative and significant effect on financial distress, and (3) financial literacy and financial behavior together have an effect on financial distress.